Molecular Techniques for identification applied to food: A review - Rafael Audino Zambelli; Isabella Montenegro Brasil (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
This review aims to address the use of molecular techniques applied to the identification of food. The application of molecular techniques in food is large, several authors comment on the detection and quantification of strains of pathogenic microorganisms present in foods and the presence of toxins and waste allergens not related to specific goods in production lines. They are also used to control the authenticity of many foods, very important for receiving raw material industries, identification of genetically modified organisms, and genetic selection in yeast for fermentation processes. The methods presented in this review proved to be fast, and effective and could be effective substitutes for chemical and physical methods, chemical and biochemical, producing results with greater accuracy, reliability and speed of analysis.